NGHIÊN CỨU CỘNG ĐỒNG VỀ MỘT SỐ YẾU TỐ DỊCH TỄ VÀ HIỂU BIẾT CỦA CHA/MẸ KHI SỬ DỤNG KHÁNG SINH CHO TRẺ TẠI THÁI NGUYÊN VÀ HÀ GIANG NĂM 2020-2021 - Hoàng, Đức Hậu; Võ, Viết Cường; Vũ, Thị Loan; Đặng, Thị Việt Hương; Phạm, Việt Hùng; Trần, Danh Tiến Thịnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
COMMUNITY STUDY ON SOME EPIDEMIOLOGICAL FACTORS AND KNOWLEDGE OF PARENTS ON USING ANTIBIOTICS FOR THEIR CHILDREN IN THAI NGUYEN AND HA GIANG PROVINCES IN 2021This study was conducted in 2020-2021 to investigate several epidemiological factors and parents' knowledge of antibiotic use in children in Thai Nguyen and Ha Giang.Methods: 459 eligible subjects were investigated for epidemiological information and knowledge of antibiotic use. 275 bacterial culture were successfully done from nasopharyl swabs of participants.Results: Some epidemiological factors such as parents' smoking, a high percentage of pipe tobacco smoking (21.6%), and up to 30.7% of relatives living in the same house (including Ha Giang at 31.4% and Thai Nguyen at 30.0%). In children, medical history of tonsillitis accounted for 37.3%, with otitis media accounting for 11.5%. The average influenza incidence was 1.7 times per year in Ha Giang and 1.9 times per year in Thai Nguyen. The proportion of children with antibiotic consumption over the past year was 47.3% in Thai Nguyen and 34.7% in Ha Giang. Commonly used antibiotics were amoxicillin and cephalexin, and most parents did not remember or knew the names of the antibiotics their children were taking. There were 42.0% of parents who knew about the use of antibiotics that the effects of antibiotics could treat bacteria. This rate was 46.9% in Ha Giang and 36.8% in Thai Nguyen, both statistical significance with p< 0.05. Of those 275 bacterial culture from nasopharyl swab, 78 (28.4%) was detected S. pneumoniae, which concordance with previous literature review.Recommendations: Conduct communication and education programs to better understand the use of antibiotics and reduce risk factors for respiratory infections. Further investigation, intervention may needed to reduce risk in S. pneumoniae carriers.